2021
DOI: 10.21608/ejhc.2021.177972
|View full text |Cite
|
Sign up to set email alerts
|

Shared Governance as A Pathway to Organizational Excellence: A Suggested Strategy for Selected University Hospital

Abstract: Background-Applying a shared governance strategy could develop collaboration between health care personnel, increase their confidence; develop their personal and professional skills; and increase their professional profile and accountability. Purpose-developing a suggested shared governance strategy for Suez Canal University hospital, Egypt: through, measuring shared governance among health care personnel at the hospital, analyzing the shared governance, and developing and validating a shared governance strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…This finding is consistent with several previous studies conducted in Jordan, Egypt, the Kingdom of Saudi Arabia, and Korea reflecting those nurses reported their perception of shared governance. [32][33][34][35][36][37] However, the results of some other studies in the abovementioned countries were inconsistent with our findings where nurses' responses corresponded to traditional governance. 38,39 Similar inconsistencies were noticed in Western and international research as well.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…This finding is consistent with several previous studies conducted in Jordan, Egypt, the Kingdom of Saudi Arabia, and Korea reflecting those nurses reported their perception of shared governance. [32][33][34][35][36][37] However, the results of some other studies in the abovementioned countries were inconsistent with our findings where nurses' responses corresponded to traditional governance. 38,39 Similar inconsistencies were noticed in Western and international research as well.…”
Section: Resultscontrasting
confidence: 99%
“…40 Many research studies have revealed lower or borderline values in the shared governance range. 33,36,37 Another explanation might be linked to a lack of transformative leadership and low involvement in shared governance. 42 These discrepancies may be related to the different types of medical institutions and differences in tasks performed and perspectives between nursing staff, depending on position and experience.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations